STRATEGI PEMASARAN DIGITAL MENGGUNAKAN INFLUENCER MARKETING DALAM PEMBUATAN VIDEO PROMOSI OUTLET OLEH-OLEH - Mirzam Arqy Ahmadi; Shobahiya, Mahasri; Brahmantya Panji Prakosa; Jihan Nur Hidayah; Erlisa Sulistianingsih (STAI Terpadu Yogyakarta, 2024)
Technological progress is currently moving rapidly, and along with technological developments, trade is also experiencing further development. Advances in technology go hand in hand with advances in knowledge. Innovation in technology exists to provide positive benefits, such as providing new, easier ways to carry out daily activities. One of them is in the field of marketing, which was previously carried out conventionally, but has now shifted to online methods via social media such as Instagram. This community service is in collaboration with UMKM Bananakrezzz which is based in Salam Village, Karangpandan. The aim of this service is to improve the skills of MSME players in marketing their products through video content uploaded on Instagram. This activity was carried out using a classical approach, involving interviews and direct practice with MSME actors in making marketing videos. The results of this activity will be a marketing video uploaded to the Bananakrezzz social media account. Participants involved include Tourism Ambassador and Lawu Princess 2023 Jhenar Agustina Putri. Collaboration with influencers has an impact on marketing videos that are made to reach more viewers and have broad insight with thousands of views. Influencer marketing influences the number of saves, likes, comments and views of the content created.